Implementação de aulas fisicamente ativas e pausas ativas em escolas de Aracaju - Silva, Marcel Belitardo da (2023)
The Erguer/Aracaju project aims to monitor the cognitive evolution and academic performance, as well as the reduction of students' sedentary behavior through movement in class. Six schools participated in the study (181 children from the first years of elementary school). Schools are divided into groups of physically active classes and active breaks and control group. For the construction of this work, empirical information was used from data collection, weekly meetings of the research team, interns' field diaries, filming of interventions and teacher training. The analysis was carried out through interviews and focus groups. The challenges in implementing the project are in the operationalization of collections and integration with the agenda and other activities of the schools. Teachers' availability of time to participate in continuing education actions is also a barrier. We observed a good acceptance of the project by principals, teachers and students, with a perspective of continuity.